THE INFLUENCE OF SERVICE QUALITY ON CUSTOMER SATISFACTION AND SERVICE (EMPIRICAL STUDY AT CELEBRITY FITNESS JAKARTA) - Robert AB; Cindy Prishila Wowor (Bina Nusantara University, 2011)
The purpose of this study is to investigate technical competence and relational competence as element of service quality (Lagrosen, 2007) contributes in customer satisfaction development. In addition the study aims to investigate the contribution of customer satisfaction to service loyalty which measured by three elements, behavior, attitude, and cognition.. This study use a combination of two research designs; descriptive and causal research design. The empirical tests using a structural equation model to support the research hypotheses. The data is collected from questionnaire, which are distributed at Celebrity Fitness in Jakarta. The research findings show that technical competence and relational competence, as a dimension of service quality has a positive relationship towards customer satisfaction. Findings also show that customer satisfaction has a positive relationship towards service loyalty. The last finding shows service loyalty is known as a multidimension structure with three dimension: behavior, attitude, cognition. This research does not compare other fitness centers. For the further research, the researcher can conduct a research in some fitness centers as a subject. It probably can be found new inventions dealing with customers’ attitude towards service quality that has a huge effect to the customer satisfaction and service loyalty. A useful foundation whereby practitioners can appreciate the importance of service quality, developing and maintaining service quality and also useful for managers of fitness companies when designing and managing fitness business. This paper presents a framework of service quality, customer satisfaction and service loyalty. This paper fulfils and identified information and resources need, and offers practical assistance to academics and practitioners in the field.